Slovenia: Empowering Families – Legal Instruments for Supporting Children, Parents, and Families Amidst Demographic Challenges - Kraljić, Suzana (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
Like other countries, the Republic of Slovenia also faces selected demographic challenges, which have significant impacts on the field of family law and family relationships. Rapid demographic changes require various measures by the authorities of the Republic of Slovenia (e.g., ministries, courts, social work centers, etc.), which provide appropriate solutions and adaptations to changing demographic structures (e.g., aging population, delayed childbirth, poverty). The author analyzes selected family law financial instruments through which the Republic of Slovenia supports families and their family members. These instruments and measures extend to many areas, which are common in their importance for the formation of the family itself (e.g., legal regulation in the field of reproductive health and assisted reproductive technologies). Likewise, instruments and measures supporting parenthood, families, and children are presented, whether from the perspective of education, healthcare, labor law, or social aspects. Changes perceived in family law in recent years are also analyzed, which have also contributed to significant demographic shifts and required legislative changes in the Republic of Slovenia (e.g., same-sex partnerships, joint adoption by same-sex partners, an increase in couples seeking medical assistance in conceiving a child). The author thus addresses and links contemporary demographic changes with measures aimed at strengthening families and addressing the diverse needs of children, parents, and families in the developing demographic context of the Republic of Slovenia. In doing so, the importance of holistic approaches addressing not only material needs but also emotional, social, and developmental aspects is emphasized, as only then can the strengthening of family and child welfare amidst the significant demographic challenges be ensured.Keywords: demographic changes, family support instruments, child’s best interest, family and child protection, reproductive health, education, parenthood